Non-toxigenic Clostridioides (Formerly Clostridium) difficile for Prevention of C. difficile Infection: From Bench to Bedside Back to Bench and Back to Bedside - Gerding, Dale N.; Sambol, Susan P.; Johnson, Stuart (Frontiers in Microbiology, 2018)
The beneficial effect of colonization of the gastrointestinal tract by non-toxigenic Clostridioides difficile (NTCD) strains as a preventive of toxigenic C. difficile infection (CDI) has been known since the early 1980s. Investigators in both the USA and United Kingdom demonstrated that prior colonization by randomly selected NTCD strains provided prevention against infection by toxigenic C. difficile in hamsters, albeit with limited durability. In the 1980s two patients with multiply recurrent CDI in the in the UK were treated with vancomycin followed by NTCD to prevent further recurrences, with one success and one failure. Epidemiologic studies of hospitalized patients using weekly rectal swab cultures demonstrated that asymptomatic colonization of patients by toxigenic C. difficile was much more common than CDI, but also that the rate of asymptomatic NTCD colonization of patients was unexpectedly high. Development of molecular strain typing of C. difficile was instrumental in characterizing different strains of both toxigenic C. difficile and NTCD leading to identification of NTCD strains that were effective human colonizers. These strains were reintroduced in hamsters in the 1990s and shown to prevent CDI efficiently and durably when challenged with epidemic toxigenic C. difficile strains. One strain of NTCD, NTCD-M3, was manufactured under cGMP standards and was demonstrated to be safe in a phase 1 volunteer trial. NTCD-M3 was then tested in a phase 2 double-blind placebo controlled trial for the prevention of recurrent CDI in patients experiencing their first CDI episode or first CDI recurrence. NTCD-M3 was given at doses of 104 or 107 spores per day orally for 7 or 14 days following successful treatment of CDI with vancomycin and/or metronidazole. CDI recurred in 30% of placebo patients and 11% of all NTCD-M3 patients (p=.006); recurrence for the best dose, 107 spores/d x 7 days, was 5% (p=.01 vs placebo). Detection of colonization predicted prevention success; among the 86 patients who were colonized with NTCD-M3 the recurrence rate was 2% vs 31% in patients who received NTCD-M3 but were not colonized (p<.001). Additional trials of NTCD-M3 for primary prevention of CDI and prevention of CDI recurrence seem warranted by these promising results.